Til erstatning for Pontoppidan - Elstad, Hallgeir (Dansk Teologisk Tidsskrift, 2009)
This article offers an analysis of some catechisms produced in the time of Enlightenment, shortly before and after 1800 in Denmark and Norway. These religion books were intended to replace Pontoppidan’s ‘explanation’ of Luther’s Minor Catechism, which had been the reader for confirmands and also in elementary school since the 1730s. Pontoppidan’s book clearly had a pietistic colour, and for both theological and pedagogical reasons the clergy influenced by the Enlightenment wanted new books. In Denmark Pontoppidan was replaced by Balle’s Lærebog i den Evangelisk-christelige religion in 1794. In Norway Pontoppidan still dominated most of the nineteenth century although alternative readers could be used in some local congregations. The following analysis shows that discipline and common duties were sharply underlined in the catechisms of the Enlightenment.